ANTHER AND OVULE DEVELOPMENT OF Johannesteijsmannia lanceolata J. DRANSF. (ARECACEAE) - Chan, Y.M.; Lim, A.L. (Malaysian Journal of Science, 2011)
The anther is tetrasporangiate with four wall layers. For the first time in Arecaceae, both Monocotyledonous and Dicotyledonous type of anther wall development are reported for a species. Cytokinesis in microsporocytes is simultaneous, forming tetrahedral (rarely isobilateral) tetrads. The pollen grains are elliptic, monosulcate with a smooth exine and are shed at the two-celled stage. The ovule is anatropous, bitegmic, crassinucellate and the micropyle is formed by both the integuments. Megasporogenesis produces linear or T-shaped (rarely) tetrads. The embryo sac development is of the monosporic, 8-nucleate Polygonum type. The antipodals are ephemeral and degenerate soon after formation. Twin archesporia and double megaspore tetrads within an ovule were observed in some sections but multiple mature embryo sacs have not been detected. ABSTRAK Anter jenis tetrasporangiat dan dinding anter terdiri daripada empat lapisan sel. Untuk pertama kali, kedua-dua jenis perkembangan dinding anter, ia itu jenis Monokotiledon dan Dikotiledon dilaporkan dalam satu spesies.Sitokinesis dalam mikrosporosit adalah serentak membentuk tetrad tetrahedral dan jarang sekali isobilateral. Debunganya eliptik, monosulkat dengan eksin licin disebarkan pada peringkat dua sel. Ovul jenis anatropous, bitegmik, krasinuselat dan mikropil dibentuk daripada kedua-dua integument. Megasporogenesis menghasilkan tetrad linear atau tetrad berbentuk T (jarang). Perkembangan pundi embrio jenis 8-nukleus monosporik Polygonum. Antipodal merosot seketika selepas dibentuk. Arkesporia dan tetrad megaspora kembar dalam satu ovul diperhatikan dalam beberapa keratan tetapi pundi embrio matang multiple tidak dapat dikesan. (Keywords: anther, pollen, embryo sac, ovule, Johannesteijsmannia)